Islam di Indonesia : Dari Little ke Greater Traditions - Saleh, Fauzan (Millah: Journal of Religious Studies, 2016)
Islam came to Indonesia when it was considerably weak either in politic, economic or military aspects. Consequently, the early presence of Islam in this country could not directly transform the whole belief systems that are irreconcilable to its principal tenets. Islam could only penetrate into the country’s cultural life through assimilation, not revolution. However, like other religions in general, Islam is always in flux. Islam is also subject to historical progress, in the sense that is evolving from "little" toward the "greater traditions" Fazlur Rahman (d. 1988) has characterized this transformation as the process of "orthodoxification" This article is an attempt to examine this transformation by scrutinizing the development of Islam in Indonesia as a part of process of orthodoxification, by focusing its consideration toward that development, up to the end of the 19th Century.